(untitled) (Innovaciones Educativas, 2023)
The following essay presents a vision of the paradigm of education in an evolutionary process of change, where from the spaces of socio-educational analysis a reflection is developed on how from past times lines of thought are followed and transformed in the system by technological and information currents, together with a different vision of new educational and administrative structures. Where the administrative management in this evolution starts from the rational principles of management, to go from the dawn of educational expansion, to the didactic facts in this expansion, along with the currents of thought. Among the duality of the changes, it is determined how the change of paradigm is difficult to eradicate and survives in education, which continues to be of production, thus maintaining a "modernization" that builds ideal molds from which we measure ourselves, compare ourselves and establish what should be; while the school system legitimizes that blaming the teacher for the educational crises is to deny that they themselves (the system) are alienated in their work. A successful educational management process must be visualized in depth, based not only on the interests of economists, but also on the individual and his or her personal development in the pursuit of successful people in all personal spheres.